1993
DOI: 10.1007/bf00004604
|View full text |Cite
|
Sign up to set email alerts
|

Stanniocalcin kinetics in freshwater and seawater european eel (Anguilla anguilla)

Abstract: The kinetics and hypocalcemic potency of stanniocalcin (STC) were examined in freshwater and seawater eels. The secretion rate and the metabolic clearance rate of STC were calculated from the STC disappearance curve after intra-arterial injection of trout STC. Basal plasma STC concentrations in freshwater and seawater eels did not differ but the STC secretion rate and metabolic clearance rate in seawater eel were 7 0 -7 5 % higher than in FW eel. The increased STC distribution space in seawater eels suggests t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Also, the metabolic clearance, secretion rate, and distribution space for STC are drastically different in freshwater and seawater eel (15). Therefore, we hypothesize that fish adapted to seawater and freshwater provide powerful models with which to study changes in PTHrP and STC activity and their influence on Mrp2-mediated transport, Mrp2 function, and Mrp2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the metabolic clearance, secretion rate, and distribution space for STC are drastically different in freshwater and seawater eel (15). Therefore, we hypothesize that fish adapted to seawater and freshwater provide powerful models with which to study changes in PTHrP and STC activity and their influence on Mrp2-mediated transport, Mrp2 function, and Mrp2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that cortisol clearance rates were higher in fully SW-adapted fish than in fully FW-adapted fish (Henderson et al 1974;Leloup-Hatey 1974). Most likely, the distribution space of the hormone is higher in SW than in FW, possibly because an in crease in perfusion of organs such as the gills (Hanssen et al 1993). Accordingly, Redding et al (1984) have demonstrated that gills of SW-adapted coho salmon take up and retain more cortisol than tissue from FW controls.…”
Section: Discussionmentioning
confidence: 99%
“…Another conclusion that can be drawn from these findings is that despite the fact that marine fish synthesize and secrete greater amounts of STC (12,14,39,40), this does not require an increase in the Ca 2ϩ sensitivity of the cells. The most likely explanations for this are the moderate hypercalcemia and CS gland hyperplasia that accompany seawater-adaptation, which together would raise the basal rate of secretion without any change in the Ca 2ϩ sensitivity of the cells.…”
Section: R1181mentioning
confidence: 84%